Exploring the Role of Islamic Career Counseling in Strengthening Work Readiness among Orphan Adolescents - Rahmah, Rizky Nurul; Yulia, Fatma; Mutiawati, Mutiawati (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
This study aims to describe the implementation of career guidance in enhancing pre-employment mental readiness among orphans at the Muhammadiyah Boys’ Orphanage, Medan Branch. The research employed a qualitative descriptive approach using a case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving caregivers, career mentors, and active foster participants in the program. The findings revealed that Islamic value–integrated career guidance significantly improved self-confidence, independence, and mental preparedness for work transition. Three key themes emerged: (1) implementation of Islamic character-based career programs, (2) enhancement of mental readiness and career orientation, and (3) mentoring strategies to overcome emotional and social challenges among orphans. These results highlight the importance of a holistic, spirituality-based approach in expanding both theoretical understanding and practical applications of Islamic career counseling within faith-based social institutions